Detecção de anticorpos anti-Rickettsia spp. em cães e equinos no estado de Mato Grosso, Brasil - Amorim, Marcus Vinicius de (2013)
Rickettsial diseases are caused by bacteria of the genus Rickettsia and family Rickettsiaceae. Among the pathogenic species for humans, only Rickettsia rickettsii, causing the Brazilian Spotted Fever (BSF), Rickettsia parkeri and Rickettsia felis have been described in Brazil. Furthermore, Rickettsia amblyommii, Rickettsia bellii and Rickettsia rhipicephali were detected and/or isolated in ticks in the country and is considered unknown pathogenicity to humans and animals. The main tick vectors inserted in the epidemiology are Amblyomma cajennense, Amblyomma aureolatum, beyond the suspected involvement of Rhipicephalus sanguineus. In areas endemic for BSF the dogs and horses have high titers of antibodies to Rickettsia spp. possibly correlated with parasitism by ticks. The study evaluated the presence of antibodies in serum samples from dogs and horses from crude antigens of R. rickettsii, R. parkeri, R. amblyommii, R. rhipicephali and R. bellii by Indirect Immunofluorescence Assay (IFA), seeking to verify the circulation of rickettsiae in the State. Samples were obtained from 384 dogs examined at the Veterinary Hospital (HOVET) in the Federal University of Mato Grosso (UFMT) in Cuiabá. Based on the map of the service units of the Institute Agricultural Defense of the State of Mato Grosso (INDEA-MT), were evaluated 460 serum samples, calculated according to the equine population of the 12 regional INDEA-MT. When a sample was positive (titers ≥ 64) for at least one antigen tested, and the titer obtained for a particular species of Rickettsia was at least four times higher than the highest one obtained for the other species can be suggested that antibodies counterparts were the first species, and is considered the probable antigen responsible for infection (PARI). Of the 11 (2.86%) samples were positive (titer ≥ 64) for Rickettsia spp. in dogs, eight determined R. bellii as PARI. For horses was determined as PARI: 131 (47.9%) samples for R. amblyommii, 13 to R. bellii (4.76%), 6 to R. rickettsii (2.19%) and 5 to R. rhipicephali (1.83%). The results showed that dogs, for BSF sentinels, had low exposure to ticks infected with Rickettsia of SFG, indicating low risk of human infection by these agents in the area. Regarding equine serum samples tested, there was a high percentage (59.3%) of animals were seropositive (titers ≥ 64) to Rickettsia spp., as well the possible movement of R. amblyommii, R. rhipicephali, R. bellii and R. rickettsii. Evidence of movement of R. amblyommii had already been confirmed in the city of Poconé-MT infecting dogs, however, was observed from this study, a wide distribution of the bacteria throughout the State. R. amblyommii ticks have been detected in the Americas and serologically associated with possible mild cases of rickettsial diseases in the United States. For R. rhipicephali and R. bellii is necessary to prove the pathogenicity for humans and animals. Despite the observation of animals exhibiting homologous antibody titers to R. rickettsii, and for this species present high lethality to humans, these data should be viewed with care, since there is no confirmation of cases in the State of BSF